Reliability model for helicopter main gearbox lubrication system using influence diagrams - Rashid, Hamad; Place, Simon; Mba, David; Keong, R. L. C.; Kleine-Beek, Werner; Romano, M. (Elsevier, 2015)
This paper presents the development of a model to assess the reliability of helicopter main gearbox (MGB) lubricating systems. The loss of oil from a helicopter MGB will lead to increased friction between components, a rise in component surface temperatures, and subsequent mechanical failure of gearbox components. A number of significant helicopter accidents have been caused due to such loss of lubrication. Current certification requirements for Category A helicopters require that gearboxes which use pressurized lubrication systems must show a capability to continue operation for a period of 30 minutes after suffering a loss of oil. This paper reports on methods for assessing reliability of pressurized MGB lubrication systems. Safety risk modeling was conducted for MGB oil system related accidents and incidents in order to analyse the key failure mechanisms and the contributory factors. As such, the dominant failure modes for lubrication systems and key contributing components were identified. The Influence Diagram (ID) approach was then employed to investigate reliability issues of the MGB lubrication systems at the level of primary causal factors. Early indications show significant benefits from this approach where multiple influences would render alternative approaches overly complex. The ID tool can systematically investigate complex context of events, conditions, and influences that are direct triggers of failures. Within this study, an ID model was introduced to describe the interrelationships between MGB lubrication system failure types. In this way the influence of each of these factors on the overall MGB lubrication system reliability may be assessed.